Leadership and power : identity processes in groups and organizations - Knippenberg, Daan van; Hogg, Michael A., 1954- (SAGE, 2003)
Leadership and associated power issues lie at the core of group life in a variety of contexts. Even the most informal of groups typically have some form of leadership in their organization, and the understanding of leadership and power from a psychological standpoint can inform a greater understanding of group dynamics both inside and outside of the workplace.